2021
DOI: 10.3390/pathogens10010068
|View full text |Cite
|
Sign up to set email alerts
|

The Remarkable Metabolism of Vickermania ingenoplastis: Genomic Predictions

Abstract: A recently redescribed two-flagellar trypanosomatid Vickermania ingenoplastis is insensitive to the classical inhibitors of respiration and thrives under anaerobic conditions. Using genomic and transcriptomic data, we analyzed its genes of the core metabolism and documented that subunits of the mitochondrial respiratory complexes III and IV are ablated, while those of complexes I, II, and V are all present, along with an alternative oxidase. This explains the previously reported conversion of glucose to acetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…It will be referred to as pap2l hereafter. This choice was primarily determined by the fact that the ortholog of this gene is absent from the genome of Vickermania ingenoplastis [34,67], a member of rather unique group of trypanosomatids that uses two joined flagella to resist midgut peristaltic flow within the fly host [35].…”
Section: Ablation Of Lgpap2l In L Guyanensis and Establishment Of The...mentioning
confidence: 99%
See 1 more Smart Citation
“…It will be referred to as pap2l hereafter. This choice was primarily determined by the fact that the ortholog of this gene is absent from the genome of Vickermania ingenoplastis [34,67], a member of rather unique group of trypanosomatids that uses two joined flagella to resist midgut peristaltic flow within the fly host [35].…”
Section: Ablation Of Lgpap2l In L Guyanensis and Establishment Of The...mentioning
confidence: 99%
“…In the current study, we have assembled and annotated the genome of LRV1-positive L. guyanensis M4147 and, by applying the CRISPR-Cas9 system, turned it into a model species by ablating a gene encoding phosphatidate phosphatase 2-like protein (LgPAP2L). An ortholog of this gene is conspicuously absent from the genome of Vickermania ingenoplastis [34,35] making it an interesting target for further investigations. In general, phosphatidic acid phosphatases (EC 3.1.3.4, PAP) are divided into two types.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent addition to the collection of trypanosomatid genomes was that of Vickermania ingenoplastis , a species lacking mitochondrial respiratory complexes III and IV and, thus, mainly relying on glycolysis, similarly to Phytomonas spp. However, in contrast to the plant trypanosomatids, the genome of this flagellate did not shrink, but experienced a substantial expansion of some protein families, in particular, the glycolytic enzymes [ 118 ].…”
Section: Other Monoxenous Lineagesmentioning
confidence: 99%
“…The analysis of myosin gene family suggested that these proteins were already diversified in the kinetoplastid common ancestor and secondarily, lost multiple times afterwards [ 127 ]. Genomic studies revealed that at least three trypanosomatid lineages—Leishmaniinae, Blastocrithidiinae, and Vickermania —independently acquired catalase from different groups of bacteria, whereas dixenous Leishmaniinae secondarily lost it [ 118 , 128 , 129 ]. The study of tubulin gene arrays demonstrated that while in the majority of trypanosomatid lineages and in the free-living bodonids that the α- and β-tubulin genes are alternated, in Leishmaniinae, these multicopy genes are organized in homogeneous (α-only and β-only) stretches [ 130 ].…”
Section: Other Applications Of the Trypanosomatid Genomic Datamentioning
confidence: 99%
“…In this group, the catalase-encoding genes were found only in monoxenous Leishmaniinae (phylogenetic relatives of dixenous Leishmania —representatives of the genera Crithidia , Leptomonas , Lotmaria and Novymonas ), Blastocrithidiinae (genera Blastocrithidia and Obscuromonas ) and Vickermania spp. Importantly, catalases in these groups have been independently acquired via HGT from bacteria of different classes: Spirochaetia (Leishmaniinae) [ 14 ] and Betaproteobacteria (Blastocrithidiinae) [ 29 ], while the origin of catalase in Vickermania has not been investigated [ 30 ]. Interestingly, the catalase-encoding gene is absent from all the analyzed genomes of Leishmania spp.…”
Section: Introductionmentioning
confidence: 99%